Cytoplasmic microtubules in two different mouse melanoma cell lines: a qualitative and quantitative analysis using confocal laser scanning microscopy and computer-assisted image analysis - Fink-Puches, Regina; Hofmann-Wellenhof, Rainer; Smolle, Josef; Helige, Christine; Kerl, Helmut (Journal of cutaneous pathology, 1997)
The microtubular system as one part of the cellular cytoskeleton is not only necessary for mitotic activity of malignant cells but also for invading neighboring tissues and for the formation of distant metastases. In the present study, the amount and distribution of tubulin in two murine melanoma cell lines (K1735‐M2: high metastatic clone; K1735‐cl16: low metastatic clone) were determined quantitatively using an indirect immunofluorescence technique, confocal laser scanning microscopy (CLSM)and computer‐assisted image analysis. Additionally, qualitative and quantitative changes after application of the microtubule‐inhibitor nocodazole were investigated. Quantitative analysis showed a significant difference between the high and low metastatic cell line for the parameter TEXTURE, indicating a finer structured network within the high metastatic cells. After treatment with nocodazole the parameters TEXTURE and DENSITY were reduced, suggesting a decrease of assembled tubulin and a less delicate structure of the remaining microtubules. Our study shows that CLSM combined with computer‐assisted image analysis provides a new method to examine quantitative variations of the cytoskeleton possibly related to cell function.